Asuhan Keperawatan Pada Tn. B Dengan Hipertensi Di Ruang Pejuang RSUD Bangkinang Tahun 2024 - Imamul Adli; Muhammad Nurman (Excellent Health Journal, 2025)
Hypertension is a disorder of the blood circulation system that causes increased blood pressure, with systolic blood pressure of 140 mmHg and diastolic blood pressure of 90 mmHg. Risk factors for hypertension include age, gender, smoking, and obesity. The purpose of this study was to examine and implement nursing care for patients with hypertension in the Pejuang room of Bangkinang Regional Hospital in 2024. This research method uses a descriptive research design in the form of a case study. The respondent in the case report was Mr. B who was 67 years old with hypertension. Data obtained through interviews, physical examinations and supporting examinations. During the assessment, the patient said that the limbs on the right side were weak, the head ached and spread to the neck and shoulders, the chest felt heavy and painful especially on the right side, the whole body felt weak, the tongue felt heavy. So that researchers can formulate the main problem with a nursing diagnosis of ineffective cerebral perfusion risk related to hypertension (D.0017). The interventions given are monitoring MAP (Mean Arterial Pressure), respiratory status, blood pressure, pulse, and body temperature. In the implementation of nursing actions on Mr. B with hypertension, it was carried out according to the nursing plan that had been prepared. The results of the four-day nursing visit to the client were resolved and the planning was maintained. The researcher's hope from writing this case report is to provide a reference in providing nursing care to patients with hypertension.